The Development of Supplement Book of Social Studies Teaching Materials of SMP., Through the Empowerment of Bali Local Wisdom as A Learning Source - Kertih, I Wayan; Sriartha, I Putu (Jurnal Pendidikan dan Pengajaran, 2022)
This research aimed at developing a Supplementary Book for Social Studies Teaching Materials through the empowerment of Balinese Local Wisdom as a Learning Resource at the SMP/ level. In achieving this goal, the research has been conducted for 3 (three) years. This research was designed as the development of research or Research and Development (R&D). This article is a research product of the first year conducted to identify and analyze Balinese local wisdom needed as Balinese Local Wisdom Textbooks material. This first-year research applied a bibliographic research design. The object of the study consisted of curriculum documents; textbooks used by teachers for social studies subjects of junior high school through the empowerment of Balinese people's local wisdom. The use of data collection techniques were interviews, observations, documentation studies, and expert judgment. The data collected was in the form of qualitative data. Processing data used non-statistical analysis. The result of the study indicated that there were various forms and types of local wisdom of the Balinese people that can be used and developed as material for the Social Studies Textbook of Junior High School with Balinese Local Wisdom.